Invention is not taught - Menezes, Flo [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2020)
in this text, composer Flo Menezes shares his impressions on teaching composition. The specific context is his experience as a selected composer at the Royaumont courses in 1995, under the supervision of British composer Brian Ferneyhough and Swiss composer Michael Jarrell, while he was writing his TransFormantes II (1995) for piano and clarinet. Menezes describes his impressions of Ferneyhough's teaching methods, on his behavior towards students, and how Ferneyhough put himself, aesthetically speaking, always in solidarity with the stundent's work. In comparison to Royaumont, he also mentions his experience as a student from Willy Correa de Oliveira in Brazil, who, on the other hand, was quite critical on the students' aesthetic decisions. Based on these encounters, Menezes discusses the specificities of teaching composition, from the benefits of musical analysis to the impossibilities of teaching inventive process.
Keywords: teaching music composition; musical analysis; new music festivals; Brazilian music